Jagad Jawa RM Kristiadi pada Proses Kreatif Program Televisi di TVRI Yogyakarta - Adji, Titus Soepono (Institut Seni Indoensia Surakarta, 2020)
ABSTRACT RM Kristiadi is a TV producer at TVRI who has been working since 1997. He is involved in programs that still exist at TVRI Yogyakarta, such as Obrolan Angkringan, Plengkung Gading, Karang Tumaritis, etc. These programs stil exist until right now, among others, because they lift the atmosphere of Javanese Culture in accordance with the principle of the similarity of body memory, the framework of fantasy that is believed in the process of its creation. RM Kristiadi also conducted experiments in building new works through critical thinking on the achievements that have ever existed. This research is a qualitative descriptive study, which focuses on knowing the background of RM Kristiadi's creative process. Data was collected through a series of direct interview processes with the interviewees, with data reinforced from documents. Key Word: Java Athmosphere, TV Produser, TV Program. ABSTRAK RM Kristiadi seorang produser televisi di TVRI yang berkarya sejak tahun 1997. Dia terlibat dalam program-program yang hingga saat ini masih eksis di TVRI Yogyakarta, seperti Obrolan Angkringan, Plengkung Gading, Karang Tumaritis, dll. Program-program tersebut eksis antara lain karena mengangkat atmosfer Budaya Jawa sesuai dengan prinsip kesamaan Memori tubuh, Kerangka fantasi yang diyakini dalam proses penciptaannya. RM Kristiadi juga melakukan eksperimentasi dalam membangun kebaruan karya melalui daya kritis atas capaian-capaian yang pernah ada. Penelitian ini merupakan penelitian Deskriptif Kualitatif, yang berfokus untuk mengetahui latar belakang alur pemikiran proses kreatif RM Kristiadi. Data dikumpulkan melalui serangkaian proses wawancara langsung pada narasumber, dengan diperkuat data-data dari dokumen. Kata Kunci: Jagad Jawa, Produser Televisi, Program Acara Televisi.